2000
DOI: 10.4049/jimmunol.164.5.2472
|View full text |Cite
|
Sign up to set email alerts
|

The Accumulation of Dendritic Cells in the Lung Is Impaired in CD18−/− But Not in ICAM-1−/− Mutant Mice

Abstract: Bone marrow-derived dendritic cell (DC) precursors migrate via the blood stream to peripheral tissues to adopt their sentinel function. To identify factors facilitating their emigration to the lung, mutant mice deficient in E-selectin, P-selectin, E/P-selectin, ICAM-1, or CD18 and their respective controls were examined. DCs and monocytes/macrophages were immunolabeled with M5/114 and MOMA-2 mAbs, respectively, and quantified morphometrically. Of these genotypes, the numbers of DC and MOMA-2+ cells were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Similar studies have also demonstrated a role for ␣ 6 integrins, which mediate adhesion to the ECM protein laminin, in Langerhans cell migration out of the skin (19). In addition to the role of integrins in DC homing to the LN, ␤ 2 integrins are critical for the homeostatic accumulation of DC within the lungs (20).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 71%
“…Similar studies have also demonstrated a role for ␣ 6 integrins, which mediate adhesion to the ECM protein laminin, in Langerhans cell migration out of the skin (19). In addition to the role of integrins in DC homing to the LN, ␤ 2 integrins are critical for the homeostatic accumulation of DC within the lungs (20).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 71%
“…47 ␤ 2 integrin also plays an important role in T cell proliferation 44 and contributes to the accumulation of dendritic cells in the lung. 48 LFA-1 and, to a lesser degree, Mac-1 contribute to neutrophil adhesion to endothelium. In a tumor necrosis factor (TNF)-induced air pouch inflammation model, neutrophil migration was equally reduced in ␤ 2 -deficient and LFA-1-deficient mice, whereas mice lacking Mac-1 showed a marked increase of neutrophil extravasation.…”
Section: Ablation Of Integrin Genes In Mice and Their Resulting Phenomentioning
confidence: 91%
“…Schneeberger et al [41] found a partial reduction in the number of DC in the lungs of CD18-deficient mice, although it is not clear whether this is due to a defect in TEM itself or to spontaneous inflammation observed in such mice [32], which might lead to subsequent depletion of DC from inflamed organs. In contrast to the data from the lung model, Grabbe et al [42] observed no differences in the migration of CD18-deficient immature DC to the inflamed skin in a model of acute contact dermatitis.…”
Section: Discussionmentioning
confidence: 99%